Effectiveness of Hand Washing Education on Knowledge, Attitude and Practice among Orang Asli Kids in Gua Musang, Kelantan - Khong, Ling Huey; Ghazali, Anis Kausar; Nik Mohd Noor, Nik Zuraina; Razian, Nur Rina Alissa; Razian, Nur Rina Alissa; Muhamad Alojid, Anis Amiera; Wan Alias, Wan Alif Syazwani; Ismail, Fauziah; Mustafa, Nor Reah; Abdullah, Cik Siti Nuraini; Awang, Sharizan; Mat Latif, Wan Noor Faradila Aini; et al. (Malaysian Journal of Medical Sciences, 2025)
Background: Handwashing is a crucial preventive measure against illnesses such as diarrhoea and respiratory infections, particularly in rural communities with limited access to clean water and sanitation. Orang Asli kids often experience high rates of preventable diseases due to poor handwashing practices. This study aimed to determine the knowledge, attitudes, and practices (KAP) of handwashing among Orang Asli kids in Gua Musang, Kelantan, and to assess the impact of a targeted handwashing education intervention. Methods: An interventional study was conducted among 61 Orang Asli students from Sekolah Kebangsaan Pasir Linggi, Gua Musang, Kelantan. The intervention consisted of a structured handwashing education programme, and KAP scores were measured before and after the intervention. A paired sample t-test was used to analyse the impact of the intervention on the participants’ KAP scores. Results: The post-intervention scores for all KAP related questions were significantly higher than the pre-intervention scores (P < 0.05). Following the educational programme, there was a significant improvement in handwashing with soap, which had been poorly practised before the intervention. Year 1 students had lower baseline knowledge and attitude scores compared to older students, highlighting the need for greater focus on younger children in future programmes. Conclusion: The handwashing education programme effectively improved the KAP of handwashing among Orang Asli kids. However, the lower baseline KAP scores among younger students suggested that future interventions should focus more on early education to foster better hygiene practices and prevent the spread of infectious diseases in this vulnerable community.